Psychosocial correlates of parents' willingness to vaccinate their children against COVID-19. - Hyunmin Yu; Stephen Bonett; Ufuoma Oyiborhoro; Subhash Aryal; Andrew Kim; Melanie L Kornides; John B Jemmott; Karen Glanz; Antonia M Villarruel; José A Bauermeister (PLoS ONE)
Background Public health guidance recommended that children who are 6 months or older be vaccinated against COVID-19 in June of 2022. In the U.S., 56% of children under 17 had not received the COVID-19 vaccination in 2023. We examine parents' willingness to vaccinate their children against COVID-19 using the theory of planned behavior in order to design effective strategies to promote vaccine uptake. Methods The Philadelphia Community Engagement Alliance is part of an NIH community-engaged consortium focused on addressing COVID-19 disparities across the U.S. We surveyed 1,008 Philadelphia parents (mean age 36.86, SD 6.55; 42.3% racial/ethnic minorities) between September 2021 and February 2022, a period when guidance for child vaccination was anticipated. Structural Equation Modeling analysis examined associations between parental willingness and vaccine-related attitudes, norms, and perceived control. Covariates included parents' COVID-19 vaccination status, race/ethnicity, gender, and survey completion post-CDC pediatric COVID-19 vaccination guidelines. Subgroup analyses by race/ethnicity and gender were conducted. Results Our model demonstrated good fit (χ2 = 907.37, df = 419, p<0.001; comparative fit index [CFI] = 0.951; non-normed fit index [NNFI] = 0.946; root mean square error of approximation [RMSEA] = 0.034 with 95% CI = 0.030-0.038). Attitudes ([Formula: see text] = 0.447, p<0.001) and subjective norms ([Formula: see text] = 0.309, p = 0.002) were predictors of intention. Racial/ethnic minority parents exhibited weaker vaccination intentions ([Formula: see text] = -0.053, p = 0.028) than non-Hispanic White parents. Conclusions Parents' attitudes and norms influence their vaccination intentions. Despite the survey predating widespread child vaccine availability, findings are pertinent given the need to increase and sustain pediatric vaccinations against COVID-19. Interventions promoting positive vaccine attitudes and prosocial norms are warranted. Tailored interventions and diverse communication strategies for parental subgroups may be useful to ensure comprehensive and effective vaccination initiatives.